2014
DOI: 10.4103/2229-516x.140730
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress indices in Nigerian pesticide applicators and farmers occupationally exposed to organophosphate pesticides

Abstract: Background:Reports have clearly indicated the role of oxidative stress in the pathogenesis of organophosphate pesticides (Op) toxicity. However, there is dearth of information on which group of the farm workers is more at risk of Op-induced oxidative stress.Aim:This study determined serum levels of malondialdehyde (MDA), catalase (CAT), glutathione peroxidase (GPx), reduced glutathione (GSH), myeloperoxidase (MPO), nitric oxide (NO), and serum activity of acetylcholinesterase (AChE) in farm workers exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
(31 reference statements)
7
10
0
Order By: Relevance
“…This is similar to what Aly et al [32], Surajudeen et al [33] reported when mice and farmers were exposed to pesticides respectively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is similar to what Aly et al [32], Surajudeen et al [33] reported when mice and farmers were exposed to pesticides respectively.…”
Section: Discussionsupporting
confidence: 78%
“…Significant reduction in SOD, CAT and GPx activity might be an indication of accumulation of H 2 O 2 that required to mump up these reactive species. Our observation possibly depicts increased formation of free radicals that could lead to oxidative damage [33,35] as a result of overwhelming antioxidant activities of all these enzymes. In other way round, GSH and TAS were significantly decreasing from 7 days through 41 days among exposed groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Milatovic, Gupta, and Aschner (2006) the agricultural pesticides promote the oxidative phosphorylation inhibition in the central nervous system, debilitating the cells capacity to keep their energy levels, what possibly increases the quantity of reactive oxygen species and reactive nitrogen species in the organism, characterizing the oxidative stress condition. This mechanism has also been pointed as relevant to justify the adverse effects in the farmers' health who were exposed to the agricultural pesticides (Surajudeen et al, 2014). Despite of this, the biological AChE role present in the erythrocyte membrane is not well explained, and it is known that this enzyme is present in the red blood cells and it has several similar proprieties like in the purified shape obtained from the brain tissue (Sorensen, Gentinetta, & Brodbeck, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphate pesticides irreversibly inhibit acetylcholinesterase to induce excessive cholinergic stimulation (2, 3). The potential off-target health consequences of organophosphate pesticide exposure for humans include neonatal developmental abnormalities (4, 5), endocrine disruption (6), neurodegeneration, cancer (7,8), metabolic disruption (9), heart disease (10), chronic kidney disease, and other less common pathologies. In addition, organophosphate pesticides are reported to have negative impacts on honeybee colonies, which are critical pollinators for numerous agricultural products (11)(12)(13).…”
Section: Importancementioning
confidence: 99%